Agency - Memory - Community: der Kranz in Festszenen auf attischer Keramik Eine bildwissenschaftliche Analyse unter Berücksichtigung phänomenologischer Prämissen - Tempel, Lioba (Hamburg University Press, 2020)
This study deals with representations of wreathed figures on Attic pottery which can be assigned to the ritual contexts of the festivities in honour of deities in archaic-classical times by means of proven pictorial elements. The aim of the work is to show the significance of the wreath in the sphere of action of the festivals of the gods. One of the priorities is the botanical determination of the different types of leaves because the different wreath representations can be used to determine fixed contexts. Furthermore, the symbolic meaning of the wreath as well as the perception processes of observers of ritualised actions are worked out. The investigation opens up new perspectives by combining different methodological approaches and interdisciplinary contents: it also encourages further research possibilities.